Survey on Customer Relationship Management Analytics - M, Varun Vijayanand; N, Deepamala (International Journal of Computer Sciences and Engineering, 2020)
With a rapidly growing customer base, it has become increasingly difficult for companies to manage and understand customer data, even with the assistance of Customer Relationship Management (CRM) platforms. The vast progress achieved in the field of Data Analytics has made it possible to extract meaningful information from raw customer data efficiently, using which well-informed decisions can be made to enhance customer relationships. This paper discusses the power of Data Analytics and CRM platforms working in unison, known as CRM Analytics. It covers the various applications of CRM Analytics and the key data mining techniques used by business organizations. A comparison between top CRM platforms is carried out and a case study on the latest cloud-based Salesforce CRM platform is presented.